The history of emotions: what the affect of the past tells us - Barrera, Begoña; Sierra, María (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article presents a critical reflection on the historiography dedicated to the study of emotions, showing its origin, achievements and possibilities. For this, the text is organized in three sections which explore: 1) the explanatory paradigms of emotions which have influenced historiographic approaches; 2) the interest that affect has provoked in contemporary historiography from the early 20th century to the arrival of the so-called «affective turn»; and 3) the plurality of theoretical approaches and categories of analysis which historians of emotions have been offering in the last few decades. Taking the above into consideration, this article defends how appropriate it is to create a dialog between the history of emotions and different categories of analysis, such as gender or race, and how beneficial it is to address these studies from different approaches, such as biographical history.